Differential activation of Fas (CD95) mediated apoptosis by apple procyanidins in human colon cancer cells SW480 and their derived metastatic cells SW620 (2011)
ABSTRACT: Introduction: We investigated the effects of apple procyanidins (Pcy), oligomers of catechins and epicatechins on Fas receptor expression and function in human colon adenocarcinoma cells (SW480) and in their derived metastatic cells (SW620). Methods: Pcy were characterized by reverse-phase HPLC. Cell death, Fas proteins, DNA fragmentation, and mitochondrial membrane potential were analyzed by flow cytometry. Fas mRNA was analyzed by RT-PCR in real time. Results: Pcy up-regulated the expression of the Fas receptor at the cell surface of both cell lines but activated Fas genetranscription only in SW620 cells. In SW480 cells, Pcy combined with Fas agonist CH-11 enhanced Fas-mediated apoptosis involving the loss of mitochondrial membrane potential and DNA fragmentation, which were abrogated by the antagonist antibody of Fas receptor, the anti-Fas ZB4. On the contrary, in SW620 cells, CH-11 was not able to enhance Pcy-triggered apoptosis indicating that Fas receptor-mediated apoptosis was not activated in these cells despite an up-regulation of Fas receptor gene expression. However, it was observed in SW620 cells that Pcy activated the Fas receptor-mediated apoptotic pathway after a specific blockage of TRAIL-death DR4/DR5 receptors. Conclusions: The present data showed that Pcy were able to activate the Fas receptor apoptotic pathway in SW480 cells and favored a cross-talk between TRAIL and Fas receptors in SW620 cells because specific blocking of TRAIL death receptors favored activation of the Fas receptor-mediated apoptosis. These important data may allow the emergence of new therapeutic protocols targeting death receptors against resistant metastatic cells.